1991
DOI: 10.1037/0096-1523.17.4.902
|View full text |Cite
|
Sign up to set email alerts
|

Automatic processes in word perception: An analysis from illusory conjunctions.

Abstract: When asked to report the color of a target letter in a briefly presented word or pseudoword, Ss were more likely to report the color of letters from the same syllablelike unit than the color of other letters. Because Ss were not required to make a lexical decision or naming response, the multiletter units that are revealed by this task arise automatically. It was found that the syllablelike units are not phonological but correspond to orthographic patterns and morphemes. These units affect performance regardle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
61
0
7

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 64 publications
4
61
0
7
Order By: Relevance
“…Another major source of evidence in favor of the notion of an early orthographic chunking mechanism is based on the illusory conjunction task (e.g., Prinzmetal et al, 1986; see also Doignon & Zagar, 2005;Prinzmetal, Hoffman, & Vest, 1991;Rapp, 1992). Especially, Prinzmetal et al (1986) showed that syllable-sized units extracted from English written words were mainly determined by orthographic and morphological factors and that phonology did not seem to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…Another major source of evidence in favor of the notion of an early orthographic chunking mechanism is based on the illusory conjunction task (e.g., Prinzmetal et al, 1986; see also Doignon & Zagar, 2005;Prinzmetal, Hoffman, & Vest, 1991;Rapp, 1992). Especially, Prinzmetal et al (1986) showed that syllable-sized units extracted from English written words were mainly determined by orthographic and morphological factors and that phonology did not seem to play a role.…”
Section: Introductionmentioning
confidence: 99%
“…One central question in the study of compound recognition has been whether the spatial and conceptual unification of solid compounds is reversed during the recognition process-that is, whether the constituents of the comp pound are discerned and accessed before the overall word is recognized. The bulk of the available empirical evidence indicates that such decomposition indeed takes place.Experimental effects of compound decomposition have b been obtained when either individually presented compound words or words related to compound word primes were to b be named or classified (see, e.g., Coolen, van Jaarsveld, & Schreuder, 1991, 1993Inhoff & Topolski, 1994;Laudanna, Badecker, & Caramazza, 1989;Libben, Derwing, & de Almeida, 1999;Lima & Pollatsek, 1983;Prinzmetal, 1990;Prinzmetal, Hoffman, & Vest, 1991;Sandra, 1990;Shillcock, 1990;Taft, 1985;Taft & Forster, 1976;van Jaarsveld & Rattink, 1988;Zwitserlood, 1994). Decompositional effects have also been obtained when compound words were viewed during sentence reading (Andrews, Miller, & Rayner, 2004;Bertram & Hyönä, 2003;Hyönä & Pollatsek, 1998;Inhoff, Briihl, & Schwartz, 1996;Inhoff, Radach, & Heller, 2000;Juhasz, 2007;Juhasz, Inhoff, & Rayner, 2005;Juhasz, Starr, Inhoff, & Placke, 2003;Pollatsek, Hyönä, & Bertram, 2000).…”
mentioning
confidence: 99%
“…with letters printed in various colors were presented, ICs of letters and colors within syllables were more likely than ICs between letters and colors in different syllables (Prinzmetal, Hoffman, & Vest, 1991). Prinzmetal and Keysar (1989) demonstrated that if context shifted syllable structure, it also affected ICs.…”
mentioning
confidence: 99%